A simulation framework for predicting occupant thermal sensation in perimeter zones of buildings considering direct solar radiation and ankle draft. (October 2020) - Zhang, Shengbo; Fine, Jamie P.; Touchie, Marianne F.; O'Brien, William
Abstract: Buildings with highly glazed envelopes have gained popularity in recent decades. Though it is well understood that these modern buildings can be less energy efficient, only a few attempts have been made to examine the impact of certain building design decisions, such as window characteristics, on indoor thermal sensation and thermal comfort. While conventional assessment of thermal sensation and comfort primarily considers zone-level environmental conditions (e.g. air temperature and relative humidity), localized effects including direct solar radiation exposure and ankle draft may also exist and can impact indoor thermal sensation especially in highly glazed perimeter zones. In this work, a simulation framework is introduced to incorporate the solar radiation effect and ankle draft effect, which are shown to increase warm and cold thermal sensation levels, respectively. The novel proposed ankle draft model adapts local draft conditions to determine the impact on overall thermal sensation for the first time. This simulation framework is demonstrated using a single-zone model using the climate of Toronto, Canada to illustrate the effect of three primary window design parameters on thermal sensation using a visualization approach: window size, U-factor, and solar heat gain coefficient. All observations are aligned with anecdotal evidence: warm thermal sensation level is positively correlated with window size and solar heat gain coefficient, whereas cold thermal sensation level is positively correlated with window size and window U-factor. This simulation framework can be used to analyze indoor thermal sensation and comfort for perimeter zones in existing buildings or fenestration alternatives during building design phases. Highlights: Direct solar radiation and ankle draft thermal sensation effects are quantified. A framework is designed for quantifying these two additional effects. A novel ankle draft model for adjusting the overall thermal sensation is proposed. Warm thermal sensation level is positively correlated with window size and SHGC. Cold thermal sensation level is positively correlated with window size and U-factor.